A Privacy-Preserving Exchange-Based Routing Protocol for Opportunistic Networks. (9th April 2022) - Jiang, Qingfeng
Abstract : In opportunistic networks, nodes forward messages according to routing utility deduced from encounter information. When nodes simply communicate with real IDs, private information such as encounter time and location will be leaked. The private information can be preserved by anonymizing node real IDs, but ID anonymity will also prevent nodes from collecting real ID-based encounter information to compute routing utility. To address this problem, a privacy-preserving exchange-based routing protocol (PPERP) for opportunistic networks is proposed in this paper. In PPERP, nodes are classified into delivery nodes and nondelivery nodes. Two encountering nondelivery nodes exchange approximately equivalent anonymous encounter records. Then, when the exchanged encounter records are sent to a delivery node, it will compute the routing utilities to nondelivery nodes without knowing their real IDs. In PPERP, a node can directly compute its routing utility without relying on any trusted third party, so PPERP is suitable for opportunistic networks in which nodes usually are sparsely distributed and encounter opportunistically. Bilinear mapping technique is adopted to ensure the confidentiality, integrity, and nonrepudiation of encounter records. The security analysis and performance evaluation show that the proposed protocol is secure, efficient, and practical.